THE RELATIONSHIP BETWEEN QUALITY OF HEALTH SERVICES AND INTEREST IN PATIENT REVISIT AT TANJUNGSARI INPATIENT HEALTH CENTER IN 2022 - Sutisna; Herawati (PHSAJ - Public Health Sebelas April Journal, 2022)
Interest in repeat visits is an attitude that arises in response to an object that shows the patient's desire to make a repurchase. During the last two months in 2022, visits to Tanjungsari Health Center were 2,641 in March and 2,142 in April, resulting in a difference of 449 visits. This study aims to determine the relationship between the quality of health services with interest in visits. The type of research used is descriptive quantitative research with a cross-sectional study approach. The sampling technique was carried out by accidental sampling technique. The sample of this study amounted to 96 patients who seek treatment at the Puskesmas. Data analysis performed was univariate and bivariate with Spearman rank test. The results of univariate analysis showed that patients who had good quality perceptions on tangible indicators (physical evidence) were 91.7%, reliability (reliability) 92.7%, responsiveness (responsiveness) 88.5%, assurance (94.8%), and empathy (empathy) 87.5% and as many as 78.1% of patients expressed interest in making a repeat visit. Then the results of the bivariate analysis showed the relationship between tangible (physical evidence) with the patient's interest in repeat visits (pvalue = 0.020), the relationship between reliability (reliability) and the interest in repeat visits of patients with (p value = 0.006), the relationship between responsiveness (responsiveness) ) with the patient's interest in repeat visits (p value = 0.001), the relationship between assurance (assurance) and the patient's interest in repeat visits with a value (p = 0.000), and the relationship between empathy (empathy) and the patient's interest in repeat visits with a value (p = 0.000). Thus, it can be concluded that there is a relationship between the quality of health services and the interest in patient return visits at the Tanjungsari Inpatient Health Center UPTD. Therefore, it is hoped that all stake holders can work together in improving the quality of health services at the Puskesmas